PHYSICAL SYSTEMS MODELING - RLC CIRCUIT GRAPHICAL SIMULATOR - Ferreira, Gabriel Fontini; Villwock, João Gabriel; Rossini, Flávio Luiz (Editora Impacto Científico, 2025)
This article presents the user manual for the application entitled: Modelagem de Sistemas Físicos - Simulador Gráfico de Circuitos RLC (SimuRLC), developed to assist students in the field of Electrical and Electronic Engineering in understanding the mathematics for analyzing RLC circuits and the application of the Laplace Transformation involved in the process. This topic is highly relevant in the current context of accelerated digital transformation, where connectivity and the advancement of the Internet are key-factors. In the industrial sector, this evolution requires the use of mathematical models as a tool to face challenges in production environments more efficiently. The manual is divided into stages: (i) Application installation; (ii) Presentation of the Laplace Transformation used; (iii) Presentation of the application interface; (iv) Case study of a circuit applied in the application; (v) Graphical validation via LTspice®. The results obtained through simulations in the application, when compared to other software, indicate good agreement and numerical stability. The conclusions obtained offer important contributions to the academic field, providing useful information for the resolution and analysis for passive RLC circuits.DOI: https://doi.org/10.56238/edimpacto2025.086-005